THE EFFECTS OF â€œONE STAYS THE REST STRAYâ€ AND â€œLOCKSTEPâ€ TECHNIQUES ON THE ENHANCEMENT OF STUDENTSâ€™READING ACHIEVEMENTS - Surjosuseno, Tjahjaning Tingastuti (Universitas Pendidikan Indonesia, 2011)
Abstract: This research was based on students? need in preliminary research which stated that most students (87%) need a new strategy in teaching and not all students have good achievements in reading texts (37.14%) in EFL classes. The writer used two-group, quasi-experimental, post test only design to investigate two techniques, i.e. ?one stays the rest stray? and ?lockstep? techniques, to increase students? achievements in EFL reading. Participants in this study included 61 college students who were taken as two intact groups. The result of statistical computations showed that the reading achievements of the experimental group increased and was significantly different from those of the control group. These students were able to have various competencies which might help keep students working on task, speaking orally, recalling the knowledge, summarizing the passage, and comprehending the text well andhappily.Keywords: one stays the rest stray technique, lockstep technique, reading achievement, positive interdependence, individual accountability and interpersonal skills.